Cross-cultural validation and psychometric properties study of the Chinese college students’ life skills scale for sport—transfer scale - Luo, Lin; He, Meilin; Wen, Shaojing; Yuan, Junfeng; Xu, Huilin (Frontiers in Psychology, 2025)
IntroductionThis study aimed to conduct a cross-cultural validation of the Life Skills Scale for Sport—Transfer Scale (LSSS-TS) among Chinese college students and examine its psychometric properties.MethodsThe study was conducted in three phases. In the first phase, four translation experts and five academic researchers collaborated to develop the Chinese version of the scale (C-LSSS-TS). Expert evaluations and feedback from 25 participants engaged in sports activities provided preliminary evidence for the scale’s construct validity. In the second phase, 409 participants were recruited, and factor analysis was performed to validate the structural dimensions of the scale. In the third phase, 168 participants completed both the C-LSSS-TS and a standard Life Skills Scale to examine the external construct validity.ResultsThe results demonstrated significant positive correlations between the subscales of sports transferable life skills and participants’ overall life skills development. These findings provided robust evidence for the structural validity of the C LSSS-TS.ConclusionThe C-LSSS-TS is a valid and practical tool for assessing life skills development among Chinese college sports participants. It offers researchers and practitioners an effective instrument to promote and evaluate life skills development in college students.